Optimization of MCM-41 Mesoporous Material Mixed Matrix Polyethersulfone Membrane for Dye Removal - Rana J. Kadhim; Faris H. Al-Ani; Qusay F. Alsalhy; Alberto Figoli (Membranes, 2021)
The aim of this work is the optimization of the operating conditions under which MCM-41-mesoporous material can be incorporated into polyethersulfone (PES)/MCM-41 membranes for nanofiltration (NF) applications. MCM-41 mesoporous material mixed matrix PES membranes have the potential to reduce membrane fouling by organic dye molecules. Process optimization and modeling aim to reduce wasted energy while maintaining high flow during the operation to handle the energy efficiency problems membranes often have. An optimization technique was applied to obtain optimum values for some key parameters in the process to produce a certain amount of flux above the desired values. Response surface methodology (RSM) and analysis of variance (ANOVA) were used as mathematical and statistical analyses to improve the performance of the process on a larger scale. This work investigated the influence of the operating parameters, such as the feed pH values (3–11), MCM-41 content (0–1 wt.%), and the feed dye concentration (10–100 ppm) for each of the two studied dyes, acid black 210 (AB-210) and rose bengal (RB), and their interactions on the PES membrane permeability. The results showed that the PES membrane had the best performance at 64.25 (L·m−2·h−1·bar-1) and 63.16 (L·m−2·h−1·bar-1) for the AB-210 and RB dyes, respectively. An MCM-41 content of nearly 0.8 wt.% in the casting solution, feed dye concentration of 10 ppm for the studied dyes, and feed pH of 3 for the RB dye was found to be the optimal parameters for eliciting the response. The pH had no significant influence on the response for the AB-210 dye, while the pH shows some minor effects on response with the RB dye, and the Pareto chart of the standardized effects on the permeation flux of both dyes using statistically significant at the 5% significance level support these results.